Manifestation Of Mine Pressure And Its Relations To Overlying Strata Movements - Z. C. Song (International Conference on Ground Control in Mining, 1982)
[THIS PAPER WAS TRANSLATED FROM CHINESE TO ENGLISH BY S. S. PENG, WEST VIRGINIA UNIVERSITY] Immediately after coal extraction, the pressure that causes the movement of the surrounding strata is called mine pressure. Through the strata movement, certain features such as supports taking load arise. This is called "manifestation of mine pressure". The existence of mine pressure is ab¬solute whereas its manifestation is relative and conditional. The visible movement of the surrounding strata occurs only when the applied pressure exceeds the plastic breaking strength. Me support begins to take load only when it offers resistance to the strata movement. The key to investigating mine pressure and its control hinges on understanding the rules and conditions for the manifestation of mine pressure. Since the face moves continuously, the mine pressure and its manifestations are also constantly changing. 'Therefore, it should not only emphasize to obtain its instantaneous magnitude, but more importantly the rules of development changes and their relations to the movement of overlying strata. Once this is resolved, one can estimate the movement of the overlying strata through mani¬festation of mine pressure and predict the time and magnitude of incoming roof weighting. Consequently the location and timing of rib excavation can be correctly selected and thus solve several major problems in the design of mining operation.